Employee Satisfaction as a key factor for their retention: A case study of Serbian Hospitality and Tourism Employees - Jankovic, Ivana; Ćirić, Miloš; Stamenković , Igor (Turizam, 2022)
Professional satisfaction of employees is certainly one of the factors towards the success of catering and tourism companies. The aim of this paper is to determine job satisfaction and see the key reasons for termination of employment in the hospitality and tourism sector. The task of the paper is to investigate, job satisfaction of employees as well as the reasons for leaving their roles. The subject of the paper are the attitudes of employees about job satisfaction in the hospitality industry. The obtained results show that the positive aspects of work are monetary stimulation, while the negative aspects are generally insufficient funds for work. As for the reasons for leaving the organization, the focus is mainly on employee dissatisfaction with the salary or some health problem.